A Refined Bead-Free Method to Identify Astrocytic Exosomes in Primary Glial Cultures and Blood Plasma - Willis, Cory M.; Ménoret, Antoine; Jellison, Evan R.; Nicaise, Alexandra M.; Vella, Anthony T.; Crocker, Stephen J. (Frontiers in Neuroscience, 2017)
Astrocytes are the most abundant glial cell type in the central nervous system (CNS) and are known to fulfill critical homeostatic functions. Dysfunction of activated astrocytes is also known to participate in the development of several neurological diseases. Astrocytes can be uniquely identified by expression of the intermediate filament protein glial acidic fibrillary protein (GFAP). Herein, we report on the development of a rigorous and sensitive methodology to identify GFAP+ exosomes in primary culture using flow cytometry. We then demonstrate that activated astrocytes release increased amounts of exosomes in response to treatment with interleukin-1β. Using this methodology, we report the identification of GFAP+ exosomes in blood and then use a mouse model of inflammatory demyelination, experimental autoimmune encephalomyelitis (EAE), to examine whether the abundance of GFAP+ exosomes in blood circulation changes during clinical illness. We find a detectable increase in the presence of GFAP+ exosomes in EAE mice when compared with non-EAE, control mice. Our data provide a novel perspective on the presence of GFAP in blood as it identifies exosomes as potential astrocyte-derived signals within blood. These data are complementary to previous clinical studies that reported elevated GFAP protein in blood samples from multiple sclerosis (MS) patients during a clinical relapse. These data also reveal the existence of a potential systemic role for astrocyte-derived exosomes in CNS conditions involving inflammation such as multiple sclerosis.